1 . Use remainder theorem to find remainder when p(x) is divided by q(x) in the
following
(a) p(x) = 2x^3 - 3x^2 + 4x - 1 q (x) = x+2
(b) x^3 - 6x^2 - 2x - 4 q (x) = 1 - 3x
2. Find the zeroes of the polynomial 3x^2 + x - 2
Answers
Answered by
22
Hiii friend,
(a) Q(X) =0
X +2 = 0
X = -2
P(X) = 2X³-3X²+4X-1
P(-2) = 2 × (-2)³ -3 × (-2)² + 4 × -2 -1
=> 2 × -8 - 3 × 4 -8-1
=> -16 -12-1 = -29
when P(X) divided by G(X) then reminder comes -29.
(B) X³-6X²-2X-4
Q(X) = 0
1-3X = 0
3X = 1
X = 1/3
P(X) = X³-6X²-2X-4
P(1/3) = (1/3)³ - 6 × (1/3)² - 2 × 1/3 -4
=> 1/27 - 6 × 1/9 -2/3 -4
=> 1/27 - 2/3 -2/3 -4
=> 1 - 18 - 18 - 108
=> -108 -36+1 = .-144+1 = -143.
When P(X) Divided by G(X) then reminder comes 73.
(C) 3X²+X-2
=> 3X²+3X-2X-2
=> 3X(X+1) -2(X+1)
=> (X+1) (3X-2)
=> (X+1) = 0. OR (3X-2) = 0
=> X = -1 OR X= 2/3
-1 and 2/3 are the two zeros of the polynomial 3X²+X-2.
HOPE IT WILL HELP YOU..... :-)
(a) Q(X) =0
X +2 = 0
X = -2
P(X) = 2X³-3X²+4X-1
P(-2) = 2 × (-2)³ -3 × (-2)² + 4 × -2 -1
=> 2 × -8 - 3 × 4 -8-1
=> -16 -12-1 = -29
when P(X) divided by G(X) then reminder comes -29.
(B) X³-6X²-2X-4
Q(X) = 0
1-3X = 0
3X = 1
X = 1/3
P(X) = X³-6X²-2X-4
P(1/3) = (1/3)³ - 6 × (1/3)² - 2 × 1/3 -4
=> 1/27 - 6 × 1/9 -2/3 -4
=> 1/27 - 2/3 -2/3 -4
=> 1 - 18 - 18 - 108
=> -108 -36+1 = .-144+1 = -143.
When P(X) Divided by G(X) then reminder comes 73.
(C) 3X²+X-2
=> 3X²+3X-2X-2
=> 3X(X+1) -2(X+1)
=> (X+1) (3X-2)
=> (X+1) = 0. OR (3X-2) = 0
=> X = -1 OR X= 2/3
-1 and 2/3 are the two zeros of the polynomial 3X²+X-2.
HOPE IT WILL HELP YOU..... :-)
Tomboyish44:
Thank you for sparing your time fo rmy doubts !!!
Answered by
10
1. ↑↑↑1st 3 images. 2.image 4....
Attachments:
![](https://hi-static.z-dn.net/files/da3/bf2a3c500d0fc39f5c7dc61b89a3832b.jpg)
![](https://hi-static.z-dn.net/files/d3a/83330741cba84a592267a2b964d34ea6.jpg)
![](https://hi-static.z-dn.net/files/d04/ed303d164b4b94fbb4d4c193e780c52a.jpg)
![](https://hi-static.z-dn.net/files/d5e/5555aa8c58fa4eba5d0371d75d512c3f.jpg)
Similar questions